The Need Analysis in Teacher Stress, Anxiety, and Depression Module Development - M.Horsi, Siti Suraiyah; Jusoh, Ahmad Jazimin; M.Horsi, Nor Samsiyah; Mohd Selamin, Intan Suhaini (International Journal of Education, Information Technology, and Others, 2024)
The needs analysis in this study was carried out to develop a module for teachers who face stress, anxiety, and depression. The research uses qualitative data collection methods using interviews with three Education Counselors and four teachers from the Malaysian Ministry of Education (KPM). The researcher has built two objectives in the study of the needs that are carried out a) exploring stress, anxiety, and depression among teachers; and b) exploring the need to develop a module for teachers who face stress, anxiety, and depression. The findings of the study show that there is a need for researchers to develop modules to help teachers who experience stress, anxiety, and depression. Based on the study's objectives, the researcher conducted an interview session with three Counselors and four teachers at the KPM and found 11 themes. Based on the findings of the needs study conducted, the researcher will focus on the themes in the development of the module.